PENGARUH MEDIA CERITA BERGAMBAR INTERAKTIF UNTUK MENINGKATKAN MINAT BACA SISWA KELAS II SD NEGERI 141 PEKANBARU - Sekar Aurora Aulia; Febrina Dafit (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the low reading interest of elementary school students, especially second grade students at SD Negeri 141 Pekanbaru. The lack of attractive and interactive learning media caused students to be less interested in reading activities. This study aimed to determine the effect of interactive picture story media on the reading interest of second grade students at SD Negeri 141 Pekanbaru. This study used a quantitative approach with a pre-experimental design using a one group pretest-posttest design. The sample of this study was second grade students at SD Negeri 141 Pekanbaru. Data collection techniques used reading interest questionnaires, observation, and documentation. The data were analyzed using statistical tests to determine the effect of interactive picture story media on students’ reading interest. The results showed that the use of interactive picture story media had a positive effect on increasing students’ reading interest. Students became more enthusiastic, active, and interested in reading activities after using interactive picture story media. Based on the results of the study, it can be concluded that interactive picture story media has an effect on increasing the reading interest of second grade students at SD Negeri 141 Pekanbaru.